TEENAGERS’ PHYSICAL, MENTAL, SOCIAL BALANCE AS A DEVELOPMENTAL PROBLEM - Rutka, Lūcija; Ušča, Svetlana; Žogla, Irēna; Kriņģele, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Promotion of teenagers’ and youth’s physical and mental health is mentioned among the priorities in the state program for the health promotion of the country’s population. Problems of teenagers’ behaviour and communication, emotional reactions, as well as their learning motives and success are often related to their health problems. The investigation verifies that the problems of balance between the teenagers’ physical, mental and social development are often under-evaluated, especially at their initial stage. This might be a reason why the above mentioned problems are un-addressed and related to teenagers behaviour and communication.Theoretical analysis and empirical investigations are guided by the background assumptions of self-conception of the teenagers, as well as balance between their physical, emotional and social development. The article analyses and interprits the differences in the teenagers’, their parents’ and teachers’ views on the problems of the above mentioned balance, as well as related to it teenagers’ emotional reactions and communication.